Upaya Meningkatkan Kemampuan Menyimak Anak Melalui Media Audio Visual Kelompok Usia 5-6 Tahun di Tk Alam Anak Negeri Tahun Ajaran 2023/2024 - Nursofiza, Nursofiza; Eliyana, Eliyana; Hamdani, Muh. (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
This research aims to improve children's listening skills through audio-visual media at the Alam Anak Negeri Kindergarten for the 2023/2024 academic year. This research was carried out at the Alam Anak Negeri Kindergarten in group B with a total of 17 children, 10 girls and 7 boys. This research uses classroom action research (PTK) techniques. The research subjects were 17 children from group B. The object of this research used data collection techniques, interviews, observation and documentation, the data analysis techniques used were qualitative and quantitative techniques, the research could be said to be successful if it reached a score or criterion of 80%. The results of the research conducted showed that audio visual media in pre-action and pre-cycle only reached 29% in cycle I, increasing to 47% in II, increasing to 82%. So it can be concluded that using audio-visual media can improve children's listening skills as seen from the increasing ability to listen to children, the level of enthusiasm and enthusiasm of children also increases because for children using audio-visual media when learning is very interesting because with audio-visual media children Children can learn to listen to interesting videos, apart from hearing they also see so that children's focus increases and is more interesting. Of course, money videos are shown according to the school theme and according to the child's age. This research was stopped in cycle II because it had reached the success criteria.